The Artistic Mastery of Luqmon Borikhan in Crafting Literary Characters - Bobojanov Alisher (International Journal Of Literature And Languages, 2025)
This article analyzes the art of character creation in Luqmon Borikhon's novel Imam Moturidi. The process of creating the character of Imam Moturidi, its historical and philosophical significance, as well as the compositional structure and plot characteristics of the novel, are examined. Additionally, the religious and philosophical views presented in the novel, artistic imagery, and the writer's attitude towards historical truth are analyzed. The article highlights that the plot of the novel is constructed in a retrospective style, with the system of characters formed based on historical sources.